AB0380 Association Between Impaired Macrovascular Function and Rheological Parameters in Patients with Rheumatoid Arthritis. (9th June 2015) - Anyfanti, P.; Triantafyllou, A.; Pyrpasopoulou, A.; Chatzimichailidou, S.; Triantafyllou, G.; Botis, I.; Panagopoulos, P.; Aslanidis, S.; Douma, S.
Abstract : Background: Impaired macrovascular function is typically encountered in rheumatoid arthritis. Systemic inflammation and autoimmune-mediated atherosclerosis inherent in rheumatoid arthritis are considered to play a primary role in the development of macrovascular disease. On the contrary, the impact of rheological properties on macrovascular function in patients with rheumatoid arthritis remains substantially understudied. Objectives: The aim of the present study was to investigate whether an association exists between macrovascular function and rheological parameters independent of inflammatory burden in a population of patients suffering from rheumatoid arthritis. Methods: Consecutive patients with rheumatoid arthritis attending the Rheumatology Outpatient Clinic of our Department were included in the study. Blood sampling was performed for the measurement of biochemical and inflammatory markers. To evaluate macrovascular function, carotid ultrasound was used for the measurement of mean carotid intima-media thickness (cIMT). The non-invasive plethysmography technique of impedance cardiography was applied to all patients to detect the properties of the blood flow in the thorax and specifically measure hemodynamic parameters including stroke index (SI), cardiac index (CI), thoracic fluid content index (TFCI), and systemic vascular resistance index (SVRI). Results: A total of 81 patients, 17 males and 64 females aged 61.8±12.2 years, with mean duration of 14.1±12.7 years of rheumatoid arthritis and a mean DAS28 score of 3.78±0.98 were included in the study. Mean body mass index (BMI) of the participants was 26.6±4.8 and mean systolic/diastolic blood pressure was 124.3±15.0/75.0±9.3 mmHg. Median erythrocyte sedimentation rate (ESR) was 16 (IQR: 10 – 29), median C-reactive protein (CRP) was 3.19 (IQR: 3.19 – 6.38) and total cholesterol levels were 205.0±34.4 mg/dl. Mean cIMT of the participants was 0.70±0.12 mm. Mean SI was 48.9±12.4 ml/m 2, mean CI was 3.4±0.8 l/min/m 2, mean TFCI was 18.2±3.5 l/kOhm/m 2, and mean SVRI was 2063.5±669.3 dyn s cm -5 m 2 . In the univariate analysis, only SVRI and CI among rheological parameters significantly correlated with cIMT (r=0.374, p=0.001 and r= -0.283, p=0.014, respectively). A significant association was observed between cIMT and ESR (r=0.304, p=0.024), but neither with DAS28 nor CRP. After adjustment for other parameters (age, sex, BMI, ESR, systolic blood pressure, cholesterol levels) in the multiple regression model, SVRI remained a significant independent predictor of cIMT (p=0.023). Conclusions: Using non-invasive, easily applicable, low-cost technology, the present study demonstrates for the first time that impaired carotid vascular wall appears to be associated with hemodynamic parameters in rheumatoid arthritis patients, independent of inflammation and other factors potentially interfering. Whether appropriate pharmacological modification of hemodynamic parameters might result in an improvement of macrovascular function in patients with rheumatoid arthritis, and vice versa, warrants future studies. Disclosure of Interest: None declared